2020
DOI: 10.1002/sctm.20-0191
|View full text |Cite
|
Sign up to set email alerts
|

The vascular nature of lung-resident mesenchymal stem cells

Abstract: Human lungs bear their own reservoir of endogenous mesenchymal stem cells (MSCs). Although described as located perivascular, the cellular identity of primary lung MSCs remains elusive. Here we investigated the vascular nature of lung-resident MSCs (LR-MSCs) using healthy human lung tissue. LR-MSCs predominately reside within the vascular stem cell niche, the so-called vasculogenic zone of adult lung arteries. Primary LR-MSCs isolated from normal human lung tissue showed typical MSC characteristics in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 73 publications
2
38
0
Order By: Relevance
“…Although the exact location of LR-MSCs remains under debate, recent studies found that human LR-MSCs express the so called “HOX code” characteristic of vascular wall MSCs (VW-MSCs derived from the vascular wall of adult human blood vessels) therefore pointing at a vascular nature. According to this picture, LR-MSCs would be located within two areas: 1. a vascular niche situated at the perivascular space between the vessels and the surrounding tissue, and 2. an alveolar niche in close contact with the capillary endothelial cells and the alveolar epithelial cells ( Steens et al, 2021 ).…”
Section: The Role Of Lung Resident Mesenchymal Stromal/stem Cells In Lung Homeostasis Injury and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact location of LR-MSCs remains under debate, recent studies found that human LR-MSCs express the so called “HOX code” characteristic of vascular wall MSCs (VW-MSCs derived from the vascular wall of adult human blood vessels) therefore pointing at a vascular nature. According to this picture, LR-MSCs would be located within two areas: 1. a vascular niche situated at the perivascular space between the vessels and the surrounding tissue, and 2. an alveolar niche in close contact with the capillary endothelial cells and the alveolar epithelial cells ( Steens et al, 2021 ).…”
Section: The Role Of Lung Resident Mesenchymal Stromal/stem Cells In Lung Homeostasis Injury and Repairmentioning
confidence: 99%
“…To date, given the poor functional characterization of LR-MSCs related to the bone marrow counterpart, their role in the lung homeostasis and pathologies should be inferred both from the studies published on LR-MSCs ( Steens et al, 2021 ), and essentially from studies based on the comparison of those to BM-MSCs. Indeed, a deeper characterization of LR-MSCs, with more in vitro and in vivo studies that will recapitulate both the spatial location and the functional effects of these cells in the lung would clarify their role within lung tissue microenvironment to enrich the knowledge in the LR-MSCs biology in order to perform new and effective LR-MSCs-based therapy.…”
Section: The Role Of Lung Resident Mesenchymal Stromal/stem Cells In Lung Homeostasis Injury and Repairmentioning
confidence: 99%
“…Due to the heterogeneous nature of the tumor stroma, there is a hitherto lack of definitive tumor stroma-derived biomarkers and of particularly (tumor-associated) MSC-specific biomarkers. The identification of such would allow to specify and improve risk stratifications and prognosis predictions for lung cancer patients [ 33 , 38 , 45 ]. Accordingly, a newly established microenvironment mimetic in vitro cell culturing system for isolation and expansion of stromal progenitors from ex vivo cultured lung tumor specimen confirmed that lung cancer MSCs played a dominant role for the maintenance of cancer stem cell populations [ 46 ].…”
Section: The Tumor-promoting Action Of Lung Cancer-associated Mscsmentioning
confidence: 99%
“…As the most originating sites of the different lung cancer types were correlated with the areas of distinct epithelial cells and their progenitor cells, even LR-MSCs could hypothetically lead to de-differentiation of lung stem cells, thereby initiating lung cancer; or at least differentiate into (divers) non-tumorigenic stromal cells that ultimately define the histological type of NSCLC [ 12 , 16 , 33 ]. Conformingly, MSC-related marker expressions (e.g., CD90, CD44, CD105, CD73 as well as LR-MSC specific HOX transcription factors) were associated with low pathologic stage in NSCLC and/or accounted for a reduced overall survival of respective patients [ 47 , 48 , 49 , 50 ].…”
Section: The Tumor-promoting Action Of Lung Cancer-associated Mscsmentioning
confidence: 99%
See 1 more Smart Citation